JAMUR YANG BERASOSIASI DENGAN Plutella xylostella L. PADA SENTRA TANAMAN KUBIS DI KOTA TOMOHON DAN KECAMATAN MODOINDING - Waywind Soewarno; Betsy A.N. Pinaria; Christina L. Salaki; Odi R. Pinontoan (Universitas Sam Ratulangi, 2013)
ABSTRACTThe aims of the research is to identify the fungi associated with the death P. xylostella larvae. The research was carried out during 3 (three) months i.e. started from August until November 2012, which is located in the Tomohon City and District of Modoinding. Working procedures of the study include: (1) a collection of the death P. xylostella larvae by taking samples along with cabbage leaves, (2) identification of fungi associated with dead P. larvae xylostella through macroscopic and microscopic observations and isolation on PDA + AB medium by direct plating and dilution. The results showed that there are five species of fungi of the death P. xylostella larvae, namely Hirsutella sp. , Metarhizium sp, Penicillium sp., Fusarium sp., and Aspergillus sp. The species of fungi Hirsutella sp. and Metarhizium sp. including entomopathogenic fungi, while Penicillium sp., Fusarium sp., and Aspergillus sp. may be opportunistic or saprophyte.Keyword: Dead P.xylostella larvae, entomopathogenic fungi, opportunistic fungi